A comparative history of Catholic and Aš'arītheologies of truth and salvation : inclusive minorities, exclusive majorities - Abdelnour, Mohammed Gamal (Currents of encounter : studies in interreligious and intercultural relations, 2021)
"In A Comparative History of Catholic and Aš'arī Theologies of Truth and Salvation Mohammed Gamal Abdelnour analytically and critically compares the historical development of the Catholic theologies of truth and salvation with those of its Islamic counterpart, Aš'arism. The monograph moves the discussion from individual theologians to theological schools with a view to helping consolidate the young field of Comparative Theology. It serves two types of readers. First, the specialist who wants to dig deeper into the two traditions parallelly. Second, the generalist who may not have the time to become thoroughly familiar with every aspect of Christian-Muslim theologies. Both readers will come out with a holistic understanding of the development of Christian and Muslim theologies of truth and salvation; a holistic understanding that increases the appetite of the former and quenches that of the latter. Despite the holistic nature of the monograph, attention is duly paid to the specificities of each tradition in a deep and profound manner"--